POLITICS OF NGOS IN POLITICAL CRIMES - Asghar Ranjbar, Ali; Hassan Hassani, Mohammad; kord alivandi, Rohodin (Revista Gênero e Interdisciplinaridade, 2020)
Non-governmental organizations, which today are seen as a manifestation of participatory criminal policy, play an important role in the realization of victims’ rights in most crimes, which is known as the policy of the Samans; But the question is, can this also play a role in political crime? Political crimes, which have been widely defined, can have broad meanings, and political crimes in the present article refer to crimes that are in conflict with the basis of the revolution. And as a crime under specific and general laws provided by law; therefore, in this type of crime, which is also a specific crime and is often unforgivable, and until they have a private aspect, the Samans must examine how the Samans can intervene. However, in addition to the supportive aspect of the Samans, it can be stated that the Samans can act in their other role as the declarants of a political crime, which the legislature also mentioned in Article 66 of the Criminal Procedure Code adopted in 1392. And although the obvious feature of the Samans is their non-profit and non-political nature.